EVALUASI PEMELIHARAAN TAMAN PADA KAWASAN THE ANVAYA BEACH RESORT BALI - Reynard, Timothy; Kohdrata, Naniek; Gunadi, I Gusti Alit (MAESTRO, 2024)
The Anvaya Beach Resort is a resort located in Tuban, Kuta, Badung. This resort has a garden with a minimalist concept, namely a combination of old and modern Bali. Garden maintenance at this resort is part of housekeeping division, however garden management is carried out by a third party, namely the contractor company Tunjung Mekar Berseri using an outsourced system. The aim of this research is to find out whether the existing resort park maintenance system meets standards or not and to provide recommendations. The data collection techniques used were observation, interviews, questionnaires and literature study. Data analysis in the form of work capacity which influences the maintenance and visuals of the park. The results of the research show that the effectiveness of garden maintenance is known for only 2 activities, namely sweeping and watering using a hose, because the activities of sprinkler watering, pruning, fertilizing, weeding, loosening the soil, and controlling pests and plant diseases are carried out incidentally. Results of effectiveness calculations maintenance on sweeping shows that in shift 1, areas A, B, D and E are below standard because these areas have a relatively small area compared to area C, the result of which is that they exceed the standard for softscape elements. Softscape and hardscape elements in shift 2 areas A and B, obtained results below the reference standard. This is due to the addition of areas between shift 1 and 2. The results show that the effectiveness of watering exceeds the reference standard with an effectiveness value of 147% in area A and 144% in area B. The recommendations given are to improve the park design, replace outsourcing staff for maintenance could be better, and improve facilities for workers.